ANALISIS PENGARUH KECEPATAN SUDUT TERHADAP PUTARAN PROPELLER DAN KESTABILAN QUADCOPTER - Alias Uto Purba; Bekti Yulianti (JURNAL TEKNOLOGI INDUSTRI, 2019)
Quadcopter is one of the Unmanned Aerial Vehicles (UAV) or the so-called unmanned aerial vehicle which is a flying vehicle that has the ability to operate without a pilot on board. A Quadcopter must consist of the following important components: - The quadcopter consists of 4 motor brushles and each motor has 1 propeller. - The quadcopter can perform several basic functions including pitch, roll and yaw - The system built into the Quadcopter is automatic.In designing this tool is to make a block diagram as a reference for each block, each of which is related to one another, thus forming a control system with a microcontroller controlled via RC (Remote Control) media.To make a quadcopter so that it can fly, a force of F is needed, for this position the force F required must be less than 6,37 kg m/.Keyword : Quadcopter, UAV, multicopter